Vivid rhetoric and visual persuasion: Ekphrasis in early Christian literature - Henning, Meghan; Neumann, Nils (William B. Eerdmans Publishing Company, 2024)
"A collection of essays exploring vivid visual rhetoric in early Christian literature"--